2017
DOI: 10.1007/s11999-016-5137-0
|View full text |Cite
|
Sign up to set email alerts
|

The Femoro-Epiphyseal Acetabular Roof (FEAR) Index: A New Measurement Associated With Instability in Borderline Hip Dysplasia?

Abstract: Background The definition of osseous instability in radiographic borderline dysplastic hips is difficult. A reliable radiographic tool that aids decision-makingspecifically, a tool that might be associated with instability-therefore would be very helpful for this group of patients. Questions/purposes (1) To compare a new radiographic measurement, which we call the Femoro-Epiphyseal Acetabular Roof (FEAR) index, with the lateral centeredge angle (LCEA) and acetabular index (AI), with respect to intra-and intero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(177 citation statements)
references
References 23 publications
(31 reference statements)
4
161
2
3
Order By: Relevance
“…Our study showed that borderline dysplastic acetabulum has significantly enlarged curvature in the anterior zone compared to the control. Although the zonal‐acetabular curvature and the FEAR index differ in the underlying biomechanical concept, both our research and recent reports based on the FEAR index suggest that borderline dysplasia may have evidence of instability 14,15 . Further investigations are necessary to evaluate whether there are correlations between zonal‐acetabular curvatures and joint instability.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Our study showed that borderline dysplastic acetabulum has significantly enlarged curvature in the anterior zone compared to the control. Although the zonal‐acetabular curvature and the FEAR index differ in the underlying biomechanical concept, both our research and recent reports based on the FEAR index suggest that borderline dysplasia may have evidence of instability 14,15 . Further investigations are necessary to evaluate whether there are correlations between zonal‐acetabular curvatures and joint instability.…”
Section: Discussionmentioning
confidence: 55%
“…Above all, the functional characterization of hip stability is important to guide surgical decision‐making. Wyatt et al 14 reported that the FEAR index, which is formed by the angle between the acetabular roof and the central third of the femoral growth plate, has a high value to predict the stability of the hip. This evaluation method is based on the biomechanical concept that the growth plate orients itself perpendicularly to the joint reacting forces during growth 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were excellent for ARO and fair to good for LCEA [41,42]. It is recognized that since we should determine the center of the femoral head to measure LCEA, the reliability of LCEA is slightly worse than that of ARO [43].…”
Section: Plos Onementioning
confidence: 99%
“…Wyatt et al hypothesized that instability of the hip could be predicted by measuring the angle between the physeal scar of the femoral head and the sclerotic sourcil of the acetabulum. 3 This was based on knowledge that the orientation and growth of the subcapital physis respond to the direction of forces applied across the hip joint during development. They refer to this measurement as the femoroepiphyseal acetabular roof (FEAR) index.…”
Section: Physical Examinationmentioning
confidence: 99%